Accumulation of Arsenic Speciation and In Vivo Toxicity Following Oral Administration of a Chinese Patent Medicine Xiao-Er-Zhi-Bao-Wan in Rats - Luo, Jiaoyang; Han, Xu; Dou, Xiaowen; Zhang, Lei; Yang, Shihai; Yang, Meihua (Frontiers in Pharmacology, 2017)
Realgar-containing traditional Chinese medicines such as Xiao-Er-Zhi-Bao-Wan (XEZBW), have been widely used for thousands of years. However, events associated with arsenic-induced ailments have increasingly become a public concern. To address the toxicity of XEZBW, we studied the histopathology and blood biochemistry of rats exposed to XEZBW using technology like high-performance liquid chromatography-inductively coupled mass spectrometry to determine arsenic speciation. Our results demonstrated that dimethylarsinic acid (DMA) increased from 18.57±7.45 to 22.74±7.45 ng/g in rat kidney after oral administration for 7 days and 14 days, which was 10-fold higher than the levels observed in controls. Trivalent arsenite As(III) showed a large increase on day 7 (26.99±1.98 ng/g), followed by a slight decrease on day 14 (13.67±6.48 ng/g). Total arsenic levels on day 7 (185.52±24.56 ng/g) and day 14 (198.57±26.26 ng/g) were nearly 2-fold higher than that in the control group (92.77±14.98 ng/g). Histopathological analysis showed mild injury in the liver and kidney of rats subjected to oral administration of realgar for 14 days. As in the XEZBW groups, a mild injury in these organs was observed after administration for 14 d. This study inferred that the toxicity of arsenic was concentration- and time-dependent. The accumulation of DMA, a byproduct of choline metabolism, was responsible for inducing higher toxicity. Therefore, we concluded that measuring the levels of DMA, instead of total arsenic, might be more suitable for evaluating the toxicity of realgar-containing TCMs.